2021
DOI: 10.1017/s0950268821001205
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy among medical students in India

Abstract: COVID-19 vaccine was launched in India on 16 January 2021, prioritizing health care workers which included medical students. We aimed to assess vaccine hesitancy and factors related to it among medical students in India. An online questionnaire was filled by 1068 medical students across 22 states and union territories of India from 2 February -7 March 2021. Vaccine hesitancy was found among 10.6%. Concern regarding vaccine safety and efficacy, hurried testing of vaccines prior to launch and lack of trust in go… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
173
4
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(198 citation statements)
references
References 26 publications
15
173
4
6
Order By: Relevance
“…The information source "social media" has been found to be associated with COVID-19 conspiracy beliefs and with higher vaccine hesitancy [42]. While international studies indicate that students often rely on social media information [40,43], we do not observe this behavior in our student body. A previous published paper found that ZHAW students' first and second choice of information source in relation to COVID-19 were public media and public health institutions and social media was only the third most frequent information source [24].…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The information source "social media" has been found to be associated with COVID-19 conspiracy beliefs and with higher vaccine hesitancy [42]. While international studies indicate that students often rely on social media information [40,43], we do not observe this behavior in our student body. A previous published paper found that ZHAW students' first and second choice of information source in relation to COVID-19 were public media and public health institutions and social media was only the third most frequent information source [24].…”
Section: Discussioncontrasting
confidence: 84%
“…The dimension calculation, referring to the correlation between individuals' engagement in extensive information-seeking behavior and decision making, had a significant influence on COVID-19 vaccination intention, but again only a small overall effect. The underlying assumption is that extensive information seeking leads to a higher exposure to vaccine-critical individuals, since critical voices are disproportionally more prominent in the internet [16], and media controversies and vaccine-critical sources have a negative impact on vaccine willingness [35][36][37][38][39][40][41]. The information source "social media" has been found to be associated with COVID-19 conspiracy beliefs and with higher vaccine hesitancy [42].…”
Section: Discussionmentioning
confidence: 99%
“…Of all 1581 respondents, only a very small fraction (0.7%, 11 respondents) positioned themselves in absolute and indisputable disagreement with COVID-19 vaccination. Worldwide, similar pro-vaccination rates were reported: 91.9% in Poland [ 10 ] or 89.4% in India [ 11 ], while only 37.3% of medical students in Uganda were willing to get vaccinated [ 12 ]. A more nuanced attitude was present in medical students from Egypt, with 71% accepting vaccination but willing to postpone it—a likely undecided stance [ 13 ].…”
Section: Discussionmentioning
confidence: 79%
“…In a computer-assisted telephone interview conducted in the general population in Romania [ 16 ], lack of trust in the COVID-19 vaccine was the primary reason (45%) for vaccine hesitancy, while the respondents of the present study rate this as the least important reason (2.7%) in their decision-making process, placing a higher importance on the speed of vaccine development. This can shed light on the impact of different sources of information, as healthcare students tend to trust public health experts [ 11 , 14 ], while media exerts a higher influence on the general public’s attitude toward vaccination [ 17 ], acceptance of COVID-19 vaccine thus being associated with the ability to detect fake news [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study conducted in Egypt [15] showed that the percentage of male students willing to take the COVID-19 vaccine was higher than their female counterparts. However, a cross-sectional study done in India [16] among medical students showed that the number of female students accepting COVID-19 vaccination was higher than those hesitant. Our finding could be attributed to the growing fears among Saudi females regarding the effect of certain COVID-19 vaccines on pregnancy and fertility since it has been wrongly assumed that COVID-19 is associated with this adverse effect.…”
Section: Discussionmentioning
confidence: 94%